Maxillary unilateral molar distalization with sliding mechanics: a preliminary investigation - (:unkn) unknown (OXFORD UNIV PRESS, 2001)
Fifteen patients, eight males and seven females with a mean age of 13.32 years, were selected for unilateral molar distalization. Dentally, all presented with a unilateral Class II molar relationship. The subjects were all in the permanent dentition with second molars erupted and with a well aligned lower dental arch. For maxillary molar distalization a new intra-oral appliance was developed, the Keles Slider, which comprised two premolar and two molar bands. The anchorage unit was a Nance button with an anterior bite plane. From the palatal side, the point of distal force application was carried towards the level of centre of resistance of the maxillary first molar. A Ni-Ti coil spring was used and 200 g distal force was applied to the Class II first molar. Lateral cephalograms were taken and analysed before and 2 months after molar distalization. The Class II molars were distalized bodily, on average, 4.9 mm (P< 0.001). Mesial migration of the Class II first premolars was 1.3 mm (P< 0.05), incisor protrusion was 1.8 mm (P< 0.05) and incisor proclination 3.2 degrees (P < 0.05). The overbite was reduced by 3.1 mm (P < 0.001) and the overjet increased 2.1 mm (P < 0.01). For stabilization, the corrected Class II unilateral molar relationship was maintained with a Nance button for 2 months. The results show that this newly developed device achieved bodily distal molar movement with minimum anchorage loss.
Keywords: DISTAL MOVEMENT; COILS